Role of Ayurveda, Lifestyle Modification, and Panchakarma Therapy on Stabilization of Atherosclerotic Plaque in Known Coronary Artery Disease Patient (International Journal of Ayurveda and Pharma Research, 2023)
Atherosclerois is a major health concern in India and imposes a significant burden on the population. The prevalence of risk factors such as hypertension, obesity, smoking and high cholesterol levels contribute to the rising incidence of atherosclerosis in the country. A 57-year-old male presented with primary complaints of chest pain and heaviness, left arm pain, upper back pain, jaw pain, dyspnea on exertion grade I, flatulence, gaseous distension, cervical pain, scapular region pain, shoulder pain, constipation, and insomnia. He also complained of postprandial angina New York Heart Association (NYHA) Class III. The patient was a photographer by profession and had a history of hypertension, diabetes mellitus, and coronary artery disease. On 29th February 2020, he underwent computed tomography (CT) coronary angiography at another clinic which revealed stenosis of the 3 main coronary arteries – more than 90% stenosis in mid left anterior descending artery (LAD), 80–90% stenosis in proximal left circumflex artery (LCx), and 80–90% stenosis in proximal right coronary artery (RCA). The patient was advised an Ayurveda-based low-carbohydrate high antioxidant diet of 1,000 calories daily for the first 12 weeks. This case report supports the relationship between an Ayurveda-based low-carbohydrate high antioxidant diet and atheroma regression in a high-risk coronary artery disease patient.